Is the road to good health paved in gold? HIV and mining in Sub-Saharan Africa. (30th September 2020) - Hansen, C; Miraldo, M; Hauck, K; Ohrnberger, J
Abstract: Background: This paper measures the impact of HIV prevalence on gold production in Sub-Saharan Africa. Gold mining adds billions of gross value to the African economy, however remains a highly-prevalent industry for HIV. Some of the largest global gold producers in South Africa estimate 30% of their workforce to be HIV-positive. In comparison, the current prevalence rate in the country is 3.7% in working-aged males. Methods: There is a reverse causality between HIV and mining. HIV exerts a direct causal influence on mining production. The mining industry creates working and living environments which accelerate the spread of HIV. Using 22 years of panel data and an external instrumental variable, overseas development assistance, supported by an Arellano-Bond estimator, we measure the causal impact of HIV on gold mining. Results: We estimate a 1% increase in HIV leads to a decrease in gold production of 9.866 tonnes, valued at over $402 million, nearly 3% of total African gold production, significant at the 10% level. These results are robust to the findings of the Arellano-Bond estimator, which are significant at the 5% level. Conclusions: International aid foundations and donors have made great strides in funding for HIV treatment, and it is critical for multinational corporations to take necessary action to protect the progress that has been made so far, promoting health and economic outcomes. Understanding macroeconomic impacts will raise the cost-effectiveness of public health interventions, and increase the associated economic benefits to many individual sectors, as well as overall local and country-wide economies. Key messages: In addition to saving lives and extending the quality of HIV-positive lives, there are economic gains to be had in investing in the prevention of HIV, as demonstrated in the gold mining industry. HIV-related productivity losses readily extend to a variety of industries across Africa and abroad. Policies that minimise these losses, and maximise health gains, can only be mutually beneficial.